Outcome in Patients with Spontaneous Primary Intracranial Hemorrhage who underwent Craniotomy Affiliation - BOON SENG LIEW; Azmin Kass Rosman; Johari Siregar Adnan (Journal of Brain And Spinal Cancer, 2016)
Background: Spontaneous primary intracranial hemorrhage or known as intracerebral hypertensive hemorrhage consist of 15 to 20% of all stroke, is one of the major health problems among healthy and productive workforce in any countries. Methods: A retrospective study was conducted in a dedicated Neurosurgical Centre at the Hospital Sungai Buloh, Malaysia. The study was conducted for admission within a year period, in the year 2013 with 6 months follow-up. A total of 35 patients were studied. Results: The mean age was 52.8 years old (31-77 years old). A total of 29 patients (82.9%) were presented with basal ganglia hemorrhage, 4 with cerebral lobar hemorrhage (11.4%) and 2 with cerebellar hemorrhage (5.7%). The surgical mortality rate was 40%. For the 6 months follow-up, 31.4% patients improved to Glasgow Outcome score (GOS) of 4, while 22.9% and 5.7% patients improved to only GOS of 3 and 2 respectively. There were several factors identified in the study to be important predictors of survival. There were statistically significance of higher mortality rate among patients with pre-operative GCS of 5 and below (p=0.015), pre-operative CT scan brain showing acute hydrocephalus (p=0.046) and residual post-operative hematoma above 5% of pre-operative clots volume (p=0.006). Other factors such as age, sex, size of pre-operative hematomas, presence of intraventricular hemorrhage, underlying medical illness were not statistically significant in predicting the surgical outcome of those patients. Conclusions: Outcome predictors such as pre-operative GCS and CT scan brain findings helps treating neurosurgeons to determine the prognosis of patients presented with spontaneous intracranial hemorrhage.
Keywords: Spontaneous Primary Intracranial Hemorrhage